2006
DOI: 10.1093/rpd/ncl127
|View full text |Cite
|
Sign up to set email alerts
|

Neutron dose measurements with the GSI ball at high-energy accelerators

Abstract: A moderator-type neutron monitor containing pairs of TLD 600/700 elements (Harshaw) modified with the addition of a lead layer (GSI ball) for the measurement of the ambient dose equivalent from neutrons at medium- and high-energy accelerators, is introduced in this work. Measurements were performed with the Gesellschaft für Schwerionenforschung (GSI) ball as well as with conventional polyethylene (PE) spheres at the high-energy accelerator SPS at European Organization for Nuclear Research [CERN (CERF)] and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The energy dependence of the capture cross sections for 3 He and 6 Li are pretty similar and our simulations showed that exchange of a TLD card with a 3 He proportional counter is possible. Exchanging the sensitive element of the dosimeter in studied layouts should provide close relative read-out.…”
Section: Dosimeter Reading Calculationssupporting
confidence: 64%
See 4 more Smart Citations
“…The energy dependence of the capture cross sections for 3 He and 6 Li are pretty similar and our simulations showed that exchange of a TLD card with a 3 He proportional counter is possible. Exchanging the sensitive element of the dosimeter in studied layouts should provide close relative read-out.…”
Section: Dosimeter Reading Calculationssupporting
confidence: 64%
“…The method calculating the amount of e.g. 3 H -particles is very suitable to estimate the dose reading of active detectors, where the dose is calculated as a number of pulses. Each pulse corresponds to a neutron capture event.…”
Section: Dosimeter Reading Calculationsmentioning
confidence: 99%
See 3 more Smart Citations